Prevalence of surgical site infection among bile spillage and non-spillage patients undergoing laparoscopic cholecystectomy: A cross-sectional study - Bhattarai, Sameer; Nalbo, Dinesh; Koirala, Sanjib; Singh, Ram Kumar (Birat Journal of Health Sciences, 2022)
Introduction: Laparoscopic cholecystectomy, a common procedure is not without complications, and bile spillage can cause surgical site infection (SSI). There is no local evidence in our hospital setting.Objective: The objective of this study was to find the prevalence of surgical site infection among bile spillage and non-spillage patients following laparoscopic cholecystectomy at BMCTHMethodology: A hospital-based cross-sectional study was conducted from 25 February 2021 to 25 August 2021 at the surgery department of BMCTH. We enrolled 120 patients through the total enumeration technique who underwent laparoscopic cholecystectomy. We enrolled all the eligible study participants who were more than 18 years excluding patients having age >75 years, acute calculous cholecystitis, evidence of cholangitis and/or obstructive jaundice, previous biliary tract surgery, or previous Endoscopic retrograde cholangiopancreatography, evidence of uncontrolled diabetes mellitus and patients taking immunosuppressive drugs and immunosuppressed conditions like HIV/AIDS. The surgical site infection was assessed on the 7th postoperative day.Results: Among 120 patients undergoing laparoscopic cholecystectomy, the majority were female 92(76.7%) and 40-50 years age group 65(54.2%). Bile spillage was found in 27(22.5%) and non-spillage in 93(77.5%).  The prevalence of surgical site infection (SSI) was found to be 7.5% which was more in the bile spillage group 25.9% than the non-spillage group 2.2%. The odds of having SSI among the spillage group was 15.9 times more than the non-spillage group and was statistically significant (p